Grammatical Cohesion in a Short Story Entitled "Matahari Ready to Be Sold" in the book "Homeless in My Own Village" by Emha Ainun Nadjib - Bagaskara Nur Rochmansyah; Ifutya Warnisa; Tiara Apriliani Widiatomo (Interdiciplinary Journal and Hummanity (INJURITY), 2025)
In linguistic studies, grammatical cohesion is one of the important aspects in discourse analysis, one of which is in literary texts such as short stories. In this study, a short story entitled "Matahari Ready for Sale" will be analyzed based on its classification. This short story not only presents an interesting storyline and social representation, but also shows the distinctive use of gramma in building meaning. This study uses a qualitative approach because this study tries to decipher language data using interpretation. In addition, the data that has been collected will be collected using a quantitative analysis model from Milles & Huberman which includes data collection, data reduction, data display (data presentation), and conclusion drawing and verification. The data that have been collected from the short story will be used to analyze the classification of the human typology and one of them is banyan man.